Identifikasi Ruang Lanskap Budaya Masyarakat Sanur, Denpasar - Bali - Sulaksana, I Gusti Candra Pertiwi; Kohdrata, Naniek; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap, 2024)
Identification of Cultural Landscape Space, Sanur Village, Denpasar - Bali ). Sanur is a village located on the coast and it’s known as a tourism area. Along with the development of tourism in Sanur goes quickly, its cause a change of shape in the structure of space patterns in Sanur. The Changes in space patterns that also have an impact on cultural landscape of Sanur society. This research aims to show the limits of development movement in Sanur so the cultural elements in Sanur would not decreased. The methods that used are survey, collecting data through field observations, interviews, and literature studies. The collected data was analyzed descriptively qualitatively with an approach to the theory of the elements city by Kevin Lynch and the theory of elements of culture by Koentjaraningrat. The results showed that the used space in Sanur was in accordance with the government regulation for Denpasar city, the changes that happen in two decades have no impact on the pattern of the cultural landscape of Sanur society. The direction of the development of cultural-based tourism that began to be applied in Sanur. It’s can help the process of preservation of cultural elements of Sanur, so sanur village still has its own characteristics.